Kids Summer Camp - Newcombe, Vanessa (Coasters Association, 2007)
In the summer of 2006, we embarked on a six (6) week summer camp pilot project in the Municipalities of Bonne Esperance and St. Augustine to provide a Youth Summer Camp for children between the ages of six to twelve. The summer camp entitled Kindness, Inspiration, Determination, Spirit, “KIDS” has proven to be a great success. This year the goal was to expand our efforts to include the communities of Chevery, La Tabatiere, and Blanc Sablon, as well as to continuing the camps already established (St. Augustine, St. Paul’s River).

Primary Health Care: Survival Pack - Buckle, Heidi (2007)

Services to the Intellectually and Physically Challenged on the Lower North Shore - Buckle, Heidi (Coasters Association, 2007)